Features of marine economic activities: classification and types in the context of marine nature-exploitation - Shurda, К. (Економіка природокористування і сталий розвиток, 2021)
The purpose of marine economic activities is to obtain economic, social, scientific, political, military and other types of effect to ensure sustainable development of Ukraine. The article discusses the characteristic features of marine economic activities, substantiates the need to clarify the widely used concept of "marine activity", given in the "Marine Doctrine of Ukraine for the period up to 2035", offers a more correct interpretation of this concept. The necessity of coordinating the actions of the entities operating in the sea space and in the coastal zone, which carry out various types of marine economic activity, is proved, possible types of marine economic activity are given. It is proposed to use the National Classifier of Ukraine "Classification of Economic Activities Types" to create a classification scheme for types of marine economic activities. The advantages and disadvantages of its application are presented, as well as the possibility of forming on its basis a detailed classification of types marine economic activity. The necessity of integrated management of marine economic activity is substantiated in order to remove existing and prevent future contradictions, as well as to coordinate the actions of economic entities. It is shown that integrated management will fully ensure the rational use of the marine environment, its resources and sustainable development of seaside regions. Particular attention in the article is paid to the issues of ecologization of the marine economic complex on the basis of the inclusion an ecological factor in the financial-economic relations of marine economic activity and the stimulation of the rational use of marine resources. The priority tasks for the construction of an economic mechanism for marine nature-exploitation have been formulated, taking into account the peculiarities of the development the seaside regions of Ukraine, the national marine policy and types of marine activities. A system of tools is presented, which are the basis for the formation of an economic-ecological mechanism of marine nature-exploitation. Метою морегосподарської діяльності визначено отримання економічного, соціального, наукового, політичного, військового та інших видів ефекту для забезпечення сталого розвитку України. Розглянуто характерні особливості цього виду діяльності. Обґрунтовано необхідність уточнення широко використовуваного поняття морська діяльність, наведеного в «Морській доктрині України на період до 2035 року» та запропоновано більш коректне трактування цього поняття. Доведено доцільність узгодження дій суб’єктів, які функціонують на морському просторі і в прибережній зоні та здійснюють різні види морегосподарської діяльності. Проаналізовано та виявлено недоліки її окремих класифікацій. Запропоновано використовувати Національний класифікатор України «Класифікація видів економічної діяльності» для створення класифікаційної схеми видів морегосподарської діяльності. Розкрито переваги та недоліки його застосування, а також можливість формування на його основі детальної класифікації досліджуваних видів діяльності. Наголошено на актуальності комплексного управління морегосподарською діяльністю з метою подолання існуючих та попередження майбутніх протиріч, а також узгодження дій господарюючих суб’єктів. З’ясовано, що таке управління забезпечить раціональне використання морського середовища, його ресурсів і сталий розвиток прибережних регіонів. Особливу увагу приділено питанням екологізації морегосподарського комплексу на підставі включення екологічного фактору в фінансово-економічні відносини морегосподарської діяльності та стимулювання раціонального використання морських ресурсів. Сформульовано пріоритетні завдання для побудови економічного механізму управління морегосподарською діяльністю з урахуванням особливостей розвитку приморських регіонів України, національної морської політики та видів морської діяльності. Наведено систему інструментаріїв, які є основою для формування економіко-екологічного механізму управління морським природокористуванням.